2008
DOI: 10.1016/j.jallcom.2007.02.083
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mechanochemical processing to luminescence properties in Y2O3 powder

Abstract: In high purity Y 2 O 3 powders presence of small amount of erbium ions in cation sites was identified due to the luminescence bands observed by Raman spectrometer. The decrease of the luminescence intensity during high-energy ball-milling was explained. The mechanochemical processing induced the changes of Y 2 O 3 microstructure introducing distortion of the crystal lattice and oxygen vacancies in the cubic phase, substitution of tungsten at the cation sites in c-Y 2 O 3 , and incomplete phase transition of Y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 31 publications
(44 reference statements)
1
21
0
Order By: Relevance
“…The XRD patterns of these powders are in good agreement with that of Y 2 O 3 (Standard JCPDS, Card no. 41-1105) crystal [9,10]. The results revealed that the precursor transformed to cubic phase of Y 2 O 3 crystals after calcination at 900…”
Section: Resultsmentioning
confidence: 96%
“…The XRD patterns of these powders are in good agreement with that of Y 2 O 3 (Standard JCPDS, Card no. 41-1105) crystal [9,10]. The results revealed that the precursor transformed to cubic phase of Y 2 O 3 crystals after calcination at 900…”
Section: Resultsmentioning
confidence: 96%
“…The Rietveld method was successfully applied for determination of the quantitative phase abundances of the composite materials and adopted in the present case [39][40][41]. …”
Section: Microstructure Evolution By X-ray Diffractionmentioning
confidence: 99%
“…The Rietveld's method was successfully applied for determination of the quantitative phase abundances of the composite materials [22][23][24][25]. …”
Section: Microstructure Evolution By X-ray Diffractionmentioning
confidence: 99%